THE MIDDLE-EARLY HYBRID OF MAIZE 'ZERNOGRADSKY 288 MV' OF A MULTI-PURPOSE USE - G. Ya. Krivosheev; A. S. Ignatiev; N. A. Shevchenko (Зерновое хозяйство России)
The breeding work on obtaining new varieties and hybrids of crops is being carried out constantly that allows developing genotypes for various soil-climatic conditions with the improved indexes of the main economic-valuable traits. A new middle-early hybrid of maize 'Zernogradsky 288 MV' has been obtained by All-Russian Research Institute of Grain Crops named after I.G. Kalinenko. According to the results of the State Variety Testing it has been introduced into the State List of Agricultural Achievements of RF and it has been approved to use in the Central-Black earth region since 2016. The hybrid of maize 'Zernogradsky 288 MV' is a three-line, middle-early (FAO 250), multi-purpose (for grain and green forage) cultivar, which belongs to the varieties with dent yellow grain, of (Zea mays L. indentata). According to the results of the competitive trial in the arid years of 2010-2012 the grain productivity was 3.40 t/ha, the green chop productivity was 25.0 t/ha. The advantage of the hybrid among the others was its high resistance to drought, high stability to lodging (only 1.3% of lodged plants) and low harvesting humidity of grain (12.2%). The new hybrid is largely tolerant to blister smut and stem rot, middle-tolerant to stem borer. The hybrid seed-growing is carried out on a sterile cytoplasm of Moldovan type CMS, the yield of seeds from all plots of hybridization is 2.0 t/ha. The new middle-early hybrid of maize 'Zernogradsky 288 MV' surpassed the standard varieties on the plots of the Central Black earth region in grain and green chop productivity. The maximum productivity of grain (10.89 t/ha) was received on the Oboyansk plot of theKurskregion, that was on 1.04 t/ha (10.6%) larger than 'Voronezhsky 279 SV'. The maximum productivity of green chop (32.69 t/ha) was obtained on theLipetskplot of theLipetskregion, that was on 9.46 t/ha (40.7%) larger than the standard variety 'Amamonte'. The introduction of the maize hybrid 'Zernogradsky 288 MV' in the agriculture of the Central Black earth region will allow increasing the gross yield of grain and green chop.